Synthesis and characterizaton of a novel bimetallic Ni-Co/Zro2 nanostructure and microstructure for steam reforming of phenol - Nabgan, Walid (CHE UTM, 2016)
The comparative catalytic activity and coke resistance are examined in steam reforming of phenol over Ni-Co/ZrO2 (NCZ) nanostructure (NS) and microstructure (MM). The NCZ-NS catalyst display more excellent catalytic activity and higher coke resistance compared with the NCZ-MS. The high resolution transmission electron microscope reveals that the predominantly exposed planes are the unusually reactive and (100) planes on the NCZ-NS rather than the stable one on the NCZ-MS. The prepared samples were also characterized by Xray diffraction, transmission electron microscopy, scanning electron microscope (SEM), Energydispersive X-ray spectroscopy (EDX) and Thermogravimetric analysis (TGA). The and (100) planes show great superiority for the anchoring of Ni nanoparticles, which results in the existence of strong metal–support interaction effect (SMSI). The SMSI effect can be helpful to prevent sintering of Ni particles, which benefits to reduce the deactivation of catalytic activity. Besides, the oxygen vacancies and the mobility of lattice oxygen also show the morphology dependence. They can participate into the catalytic reaction and be beneficial to the activation of carbon deposition. In conclusion, the excellent catalytic activity and coke resistance of the NCZNS should be attributed to the SMSI effect and abundant oxygen vacancies.